Refabrication of an implant-retained auricular prosthesis using clip attachment pickup technique - Sanketh Kethireddy; Keerthi Kethireddy (Wolters Kluwer Medknow Publications, 2017)
Increased patient acceptance and widespread use have led to a greater demand for refabrication of existing maxillofacial prostheses exhibiting wear and tear. Refabricating an osseointegrated implant-retained silicone auricular prosthesis on the existing Hader bar is a challenging task if it is performed without removing it. Therefore, an attachment level impression method is utilized for the refabrication of a new prosthesis on an existing Hader bar framework without removing it from the patient's defect. This case report discusses a modification of the Mahidol University technique. This modification provides a simple, speedy, and convenient method through which the relation between the metal framework and attachments could be obtained precisely. This precision allowed for easy fabrication of the acrylic housing, which in turn results in better adaptation of the auricular prosthesis to the patient's face. Therefore, this technique offers advantages to both the prosthetist in fabrication and the patient in facilitating him continue to wear his existing implant-retained prosthesis during refabrication process.